Characteristics of flora and vegetation of Kolmakhtun Lake – Nature Reserve of local significance of Tomsk Region (West Siberia, Russia) - Valentina P. Amelchenko; Tatiana A. Blyakharchuk; Yulia A. Kharanzhevskaya; Rinat M. Manasypov; Tatiana N. Kataeva (Acta Biologica Sibirica)
Kolmakhtun Lake is located in the center of Tomsk Region in a basin of Ob’ River. It is Nature Reserve of local significance (OOPT). A complex team of researchers from Tomsk State University performed a multi-years research of hydrology, flora and vegetation of this area. In details have been investigated flora and vegetation of Kolmakhtun Lake and surrounding area. Anthropogenic influence on the lake and surrounding vegetation have been estimated. Applied methods of research were based on multiyears descriptions of vegetation and flora and includes 30 field geobotanical descriptions, herbarium collections, photographs, results of laboratory analyses of floristic lists by elements of flora. The general species composition includes 212 species of vascular plants belonging to 55 families. Angiosperms (Magnolyophyta) dominate the taxonomic spectrum – 201 species from 52 families. The share of 10 leading families accounts for 92 species (43.4%), Asteraceae, Rosaceae and Poaceae dominate. The species composition of adventives totals 40 species, which is 18.9% of the entire flora of the lake. Five types of vegetation are described: forest, meadow, aquatic, shrub and marsh. A classification of vegetation is given, including 6 classes, 7 subclasses, 8 groups of associations and 32 associations are distinguished. Anthropogenic changes, most clearly manifested in grassland-forest and aquatic vegetation, are described. Rare species listed in the Red Books of Siberia were discovered: Salvinia natans (L.) All., Nymphoides peltata (S.G. Gmel.) Kuntze, Nymphaea tetragona Georgi and Triglochin palustre L.